1994
DOI: 10.1007/bf01421204
|View full text |Cite
|
Sign up to set email alerts
|

TRICLOPS: A tool for studying active vision

Abstract: The design, performance, and application of The Real-time, Intelligently ControLled, Optical Positioning System (TRICLOPS) are described in this article. TRICLOPS is a multiresolution trinocular camera-pointing system which provides a center wide-angle view camera and two higher-resolution vergence cameras. It is a direct~rive system that exhibits dynamic performance comparable to the human visual system. The mechanical design and performance of" various active vision systems are discussed and compared to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…To compare the performance of the different pursuit systems, with and without prediction, experiments were conducted using the NIST robot head, TRICLOPS (Fiala et al 1993), shown in Figure 14 up and down, and a fourth axis, the neck, pans the entire head. TRICLOPS is capable of high dynamic performance.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the performance of the different pursuit systems, with and without prediction, experiments were conducted using the NIST robot head, TRICLOPS (Fiala et al 1993), shown in Figure 14 up and down, and a fourth axis, the neck, pans the entire head. TRICLOPS is capable of high dynamic performance.…”
Section: Resultsmentioning
confidence: 99%
“…TRICLOPS has four mechanical degrees of freedom. The four axes are: pan about a vertical axis through the center of the base, tilt about a horizontal line that intersects the base rotation axis and left and right vergence axes which intersect and are perpendicular to the tilt axis (Fiala et al, 1994). The system is configured with two 0.59(in) vergence lenses and the distance between the two vergence axes is 11(in).…”
Section: Triclops -A Case Studymentioning
confidence: 99%
“…Only horizontally moving objects are detected, based on very high image differences without ego-motion subtraction. There are many further systems that use very simple image processing to detect and track well-defined targets like white blobs [17,18], putting emphasis on the control aspect of the problem.…”
Section: Related Workmentioning
confidence: 99%